Baseline for food waste generation – a case study in Universiti Tun Hussein Onn Malaysia cafeterias - Alias, A R; Mohd Mokhlis, N A; Zainun, Nur Yasmin (IOP Publishing, 2017)
Increasing population and economy status have contributed to the increasing volume of solid wastes produced in Malaysia and it creates problems on the existing solid waste management system. Ineffective waste management system was one of the issues that often discussed. The purpose of this study was to suggest the best method for managing food waste in Universiti Tun Hussein Onn Malaysia (UTHM) cafeterias. The scope of the study was to identify the type and quantity of waste generated in each cafeteria. The study area was carried out at six cafeteria in UTHM including residential college cafeteria which are Tun Dr.Ismail (TDI), Tun Fatimah (TF) and Tun Syed Nasir (TSN), G3’s cafeteria, Arked, and Dr. Munie’s cafeteria located at the Faculty of Civil and Environmental Engineering (FKAAS). In this study, food waste was quantified in unit of kilogram (kg). Results of the study showed that total food waste in selected UTHM’s cafeterias was 6197.5 kg for two months. Food waste generated in G3’s cafeteria was the highest value with 1823.5 kg among another cafeteria. This is due to strategic location for students and staff to take meals, the variety of food sold and reasonable price were major factors of generating food waste. Meanwhile, the Dr. Munie's Cafeteria located in FKAAS recorded the least total production of food waste as staffs and students take their meals at others cafeterias. Through literature review, there are list of methods on waste management were identified and composting method was suggested for food waste management in UTHM since the waste was produce in very large quantity.